Comparison of Thermophysical Properties of PIM Feedstocks with Polyoxymethylene and Wax-Polyolefin Binders - Alexander N. Muranov; Maxim A. Kocharov; Maxim S. Mikhailov (Civil Engineering Journal, 2024)
One of the high-performance technologies for the serial production of small-sized metal and ceramic complex-profile parts is powder injection molding (PIM). The most industrially demanded types of polymer binder in PIM technology are polyoxymethylene-based compositions and wax-polyolefin mixtures. Despite the large number of studies devoted to different compositions of polymer binder for PIM technology, the actual task is still a comparative analysis of the properties of different binder types to determine their advantages and disadvantages, as well as the optimization of the used compositions. In this regard, this study aims at a comparative analysis of the thermophysical properties of the most demanded feedstocks with binder based on polyoxymethylene and wax-polyolefin mixtures under the condition of using identical steel powder filler. The specific heat capacity, temperatures, and heat of phase transitions, as well as the thermal inertia and effective thermal conductivity of the compared types of feedstocks, were determined as a result of the calculation-experimental study. The obtained data can replenish the knowledge bases necessary for simulation modeling and optimizing powder molding processes of various products made of 42CrMo4 steel. As a result of a comparative analysis of the thermophysical properties of feedstocks with identical powders, the kinetic effects in the thermal processes of forming feedstocks with polyoxymethylene are less significant than those in analogs with wax-polyolefin binder, which facilitates their moldability. Thus, the feedstock with polyoxymethylene has a significantly higher rate of temperature field leveling than the analogs with wax-polyolefin binder. Because of the insignificant difference in specific heat capacity, feedstocks based on polyoxymethylene have 1.5 times higher effective thermal conductivity and approximately 20% higher thermal inertia than feedstocks with identical powder filler and binder in the form of a wax-polyolefin mixture. The technological advantages of feedstocks with a wax-polyolefin binder include the possibility of processing at lower temperatures. Doi: 10.28991/CEJ-2024-010-06-05 Full Text: PDF